A rare case of alveolar-capillary dysplasia in a newborn: pathomorphological aspect - Melnyk, Maiia; Pedorenko, Kateryna; Kovalchuk, Olena (The Ukrainian Scientific Medical Youth Journal, 2025)
Alveolar-capillary dysplasia is a rare congenital lung disease characterized by abnormal development of the alveoli and the capillaries that surround them. Due to abnormalities in the structure of the capillaries and their incorrect location in relation to the alveoli, problems with gas exchange arise in the lungs, which makes it impossible to effectively saturate the blood with oxygen. This disease manifests itself from the first hours or days of a child's life. Newborns have severe respiratory failure, which is not treatable by standard methods, such as oxygen supply or artificial ventilation of the lungs, and most children with this diagnosis do not survive to one month without lung transplantation. Diagnosis is made by lung tissue biopsy and histological examination, which allows to confirm the presence of structural abnormalities in the lung tissue or after performing genetic analysis to search for a mutation in the FOXF1 gene. Treatment of this disease is currently limited and mainly consists of supportive therapy. The only radical treatment is lung transplantation. This article discusses a case of alveolar-capillary dysplasia of the lungs of a newborn. The results of a postmortem morphological study of lung tissue are presented. The article will be useful for doctors of any specialty, for timely diagnosis of the disease and provision of highly specialized care.